Ploidy level of the banana (Musa spp.) accessions at the germplasm collection centre for the East and Central Africa - Karamura, Deborah; Tumuhimbise, Robooni; Muhangi, Sedrach; Nyine, Moses; Pillay, Micheal; Ssali Tendo, Reuben; Talengera, David; Namanya, Priver; Kubiriba, Jerome; Karamura, Eldad (African Journal of Biotechnology, 2016)
Banana Germplasm Collection serves as a source of useful genes for banana breeding. However, insufficient and/or inaccurate information on the ploidy level of the germplasm renders its utilization in breeding difficult. The objective of this study was to determine and validate the ploidy level of 120 banana accessions in the ex situ germplasm collection centre for the East and Central Africa, located in Mbarara, Uganda. Flow cytometric analysis of the nuclear DNA content was used to determine the ploidy level of the accessions. Results indicate that accessions: Bura, Diana, Kambani-Rungwe, Paji and Pagatau, and Rungwe that were previously classified as diploids are actually triploids, whereas Selangor previously known to be a diploid is a tetraploid. Accessions such as Galeo, Mwitupemba and Ntindi 1 that were previously classified as triploids were found diploids. GT, FHIA 25 and Muzungu Mwekundu that were considered as tetraploids, were found triploids. The information generated will guide correct placement of these accessions in the regional germplasm collection centre for the East and Central Africa and their utilization in banana breeding.
Keywords: Banana germplasm; Breeding ex situ germplasm collection; Flow cytometry, ploidy